The analysis of middle school students’ attitudes towards mathematics in terms of various variables - (:unkn) unknown (Sakarya University, 2015)
The purpose of this study is to analyze the middle school students’ attitudes towards mathematics in terms of various variables (such as their achievements in different subjects, whether they get help while doing their mathematics homework or not etc.). In accordance with this purpose the study was designed according to scanning model. The data required for obtaining the stated objective were collected through; “Personal Information Form (PIF)” and “Mathematics Attitude Scale (MAS)”. The study group is composed of 341 middle school students. 174 of the students are female (51,03%) and 167 of them are male students (48,97%). As a result of the analyses, it was appeared that the attitudes of middle school students differed significantly according to their achievements in different subjects (Mathematics, Science and Turkish). Besides, it was determined that the attitudes of students differed significantly according to their states like understanding mathematics, like playing games regarding mathematics and hope to do a profession in the future about mathematics. In addition to these, it was appeared that the attitudes of middle school student did not statistically differ according to whether they get help while doing mathematics homework, having own room and to the time allocated for studying mathematics. In this sense, it can be said that the academic achievements of students, their understanding regards mathematics, playing mathematical games and having a desire to do a profession about mathematics in the future are all important in their attitudes towards mathematics. © The Turkish Online Journal of Educational Technology.
Keywords: Achievements in lesson; Attitude; Game; Profession; Understanding